(untitled) - Slavin, Nathan S. (New York, 1985)
The book contains 12 chapters and is organized into four parts. Part one introduces the basic concepts and recording systems of a manufacturing operation. Part two analyzes the details of the three elements of product cost. Part three presents the alternative accumulation methods. Part four concludes the text with two chapters on standard cost accounting and a chapter on cost-volume-profit analysis and budgeting
Keywords: Cost accounting